(untitled) (Bangladesh Journal of Agricultural Research, 2011)
A study was undertaken to evaluate the field performance and economic analysis of some commonly used insecticides against Tea mosquito bug, Helopeltis theivora Waterhouse at Bangladesh Tea Research Institute (BTRI), Srimangal, Moulvibazar. Six different insecticides–Thiodan 35EC (Endosulfan), Ripcord 10EC (Cypermethrin), Decis 2.5EC (Deltamethrin), Dimethion 40EC (Dimethoate), Metasystox 25EC (Oxydemeton), and Malathion 57EC (Malathion) were applied in the plots as recommended dose of BTRI. The shoot infestation reduction as well as yield response of all the insecticides treated plots were superior over the control but there was no significant difference among the insecticidal treatments. Better field performance against Helopeltis was found in Malathion 57 EC treated plots in respect to shoot infestation reduction over control (87.09%). Per hectare yield (1910.33 kg) as well as per hectare net return (Tk. 300927.80) were also higher in Malathion 57EC treated plots. The highest marginal rate of return (2580.57%) was obtained by spraying Metasystox 25EC over control followed by Ripcord IOEC (1710.87%) and other insecticides. The most economically acceptable insecticide against tea mosquito bug was Metasystox. Keywords: Field performance; economic analysis; insecticides; tea; Helopeltis theivora. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9273 BJAR 2011; 36(3): 449-454